2000
DOI: 10.4049/jimmunol.165.8.4174
|View full text |Cite
|
Sign up to set email alerts
|

Vγ1+ T Cells Suppress and Vγ4+ T Cells Promote Susceptibility to Coxsackievirus B3-Induced Myocarditis in Mice

Abstract: Coxsackievirus B3 infections of C57BL/6 mice, which express the MHC class II IA but not IE Ag, results in virus replication in the heart but minimal myocarditis. In contrast, Bl.Tg.Eα mice, which are C57BL/6 mice transgenically induced to express IE Ag, develop significant myocarditis upon Coxsackievirus B3 infection. Despite this difference in inflammatory damage, cardiac virus titers are similar between C57BL/6 and Bl.Tg.Eα mice. Removing γδ T cells from either strain by genetic manipulation (γδ knockout(ko)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
124
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 44 publications
9
124
0
Order By: Relevance
“…This finding is consistent with other recent studies associating TCR-defined subsets of ␥␦ T cells with distinct functional roles (23,(25)(26)(27)(28). The requirement for a TCR-defined population also suggests that TCR-ligand recognition and the particular specific ligand of the regulatory ␥␦ T cell subset are important in maintaining normal airway function (29).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with other recent studies associating TCR-defined subsets of ␥␦ T cells with distinct functional roles (23,(25)(26)(27)(28). The requirement for a TCR-defined population also suggests that TCR-ligand recognition and the particular specific ligand of the regulatory ␥␦ T cell subset are important in maintaining normal airway function (29).…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, anti-TCR-V␥1 mAb had no effect (Fig. 2 E and F), although this Ab efficiently depletes V␥1 ϩ T cells as we have demonstrated (23). These results established the V␥4 ϩ T cell subset as a negative regulator of airway responsiveness in C57BL͞6 mice.…”
Section: Airway Responsiveness Is Regulated By Pulmonary ␥␦ T Cellssupporting
confidence: 47%
“…66 Investigation of ␥␦ T cell subsets in coxsackieviral myocarditis has shown that V␥1ϩ T cells suppress myocardial inflammation whereas the V␥4ϩ subset promoted myocarditis. 67 The V␥4 subset was found to produce interferon (IFN)-␥ and promote TH1 responses.…”
Section: Susceptibilty To Myocarditis In Rodent Modelsmentioning
confidence: 99%
“…In mice and humans, it was found that functional attributes of γδ T cells segregate with expressed γδ T-cell receptors (TCRs) (8,9), although functional differentiation has also been observed within or across TCR-defined subsets and correlated with other markers, such as CD27 and CD8 (10,11). The murine TCR-γ locus contains seven Vγ genes, six of which are functional and expressed on the cell surface (3,12).…”
mentioning
confidence: 99%